2008
DOI: 10.1016/j.clae.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Oral omega-6 essential fatty acid treatment in contact lens associated dry eye

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. and also a significant improvement in overall lens comfort at 6 months (p<0.01). Permanent repository linkTear meniscus height was increased in the EPO group at 6 months relative to baseline (p<0.01), although all other objective signs were unchanged. Conclusion:This study provides evidence for a beneficial effect of particular orally administered omega-6 fatty acids in alleviating dry eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…At the end of the study, 70% of the patients treated with omega-3 supplements became asymptomatic and Schirmer testing together with fluorophotometry suggested that the omega-3 supplement increased tear secretion. A similar improvement was reported by Kokke et al 24 in 76 patients with contact lens related DES following treatment with omega-6 supplements.…”
Section: Role Of Systemic Efas In the Management Of Desclinical Trialssupporting
confidence: 83%
“…At the end of the study, 70% of the patients treated with omega-3 supplements became asymptomatic and Schirmer testing together with fluorophotometry suggested that the omega-3 supplement increased tear secretion. A similar improvement was reported by Kokke et al 24 in 76 patients with contact lens related DES following treatment with omega-6 supplements.…”
Section: Role Of Systemic Efas In the Management Of Desclinical Trialssupporting
confidence: 83%
“…Ten trials have investigated formulations of omega-6 alone or combined with antioxidants (Aragona et al, 2005;Barabino et al, 2003;Horrobin et al, 1981;Kokke et al, 2008;Macri et al, 2003;Manthorpe et al, 1984;McKendry, 1982;Oxholm et al, 1986;Pinna et al, 2007;Theander et al, 2002). The first anecdotal report of effectiveness of omega-lipid-based dietary nutraceutical was published in 1981 (Horrobin et al, 1981).…”
Section: Omega-6 Formulationsmentioning
confidence: 98%
“…Finally, a RCT investigating the effectiveness of evening primrose oil (300 mg GLA) for contact lens dryness over 6-month demonstrated improved comfort and tear volume but no effect on tear stability, ocular surface staining or meibomian gland appearance (Kokke et al, 2008). An investigator masked notreatment control trial investigated the effectiveness of using low supplementation with 28.5 mg LA and 15 mg GLA for 1 month in patients undergoing photorefractive keratectomy (PRK) to correct their refractive error (Macri et al, 2003).…”
Section: Omega-6 Formulationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Hyperosmolarity may also induce tear film instability by activating inflammation, leading to epithelial damage that interferes with normal production of the tear film. 1,3 Combined g-linolenic (18:3n-6) and linoleic acid (18:2n-6) supplementation has shown positive effects on meibomian gland dysfunction and dry eye, [5][6][7][8][9] and consumption of n-3 fatty acids is associated with reduced risk of dry eye in women. 10 Suggested mechanisms underlying the beneficial effects of n-3 fatty acids and the combination of g-linolenic and linoleic acids include effects on inflammation, tear secretion, and tear film lipids.…”
mentioning
confidence: 99%